Formulation and evaluation of Tenoxicam Gels for Topical Use (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Tenoxicam is a non-steroidal anti-inflammatory drug that belongs to the oxicam class of derivatives. In this study, two different grades of carbopol bases 940 and 934 at a concentration of 15 % w/w were used as base. Three different polyols namely glycerin, propylene glycol and PEG-400 were added as co-solvents either alone or in combination at concentrations of 0 to 4 % w/w and using eight treatment combinations according to the 23 factorial design, an experiment was conducted. In vitro diffusion characteristics, anti-inflammatory activities and the rheological characteristics of finished formulations were studied. The in vitro diffusion studies showed that the drug release was faster in formulations containing the co-solvents glycerin(G3 and F3) and PEG-400 (G4 and F4) with carbopol 940 and 934 bases respectively. Drug release was faster from carbopol 934 gel forming base with all cosolvent gel formulations than from the carbopol 940 gel base formulations. The release data obtained for tenoxicam obeyed first order kinetics. The results from the study could be useful in preparing a marketable tenoxicam gel formulation with maximum drug release for efficacious use in inflammatory conditions at the site of pain.
Keywords: Tenoxicam; gels; carbopol; co-solvents